Designing Problem Based STAD Learning Models to Improve Students’ Writing Skill - Wida Rianti; Citra Ayu; Putri Asilestari (STAI Hubbulwathan Duri, 2021)
This research was conducted to develop a learning model by using the ADDIE model. The problem-Based STAD learning model was designed by Analysis, Design, Development or Production, Implementation or Delivery, and Evaluations. This research was done in the English Language Education Study Program of the University of Pahlawan Tuanku Tambusai in Writing II. Based on the result of data analysis, it can be concluded that 1) The Problem-based STAD Type Learning Model has been produced through the ADDIE development model. 2) Problem-based STAD Type Learning Model that has met the criteria of validity. 3) The model is valid with the characteristics of the suitability of the research model development with the ADDIE procedure. English teachers can use this model to improve students’ skills in writing and motivate the students in writing English text.